2008
DOI: 10.1177/1082013208095686
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Winemaking Processes for Red Wine Color Enhancement

Abstract: The effects of five novel winemaking technologies on color were evaluated. Cold soak maceration (CSM), dry ice maceration (DIM), prefermentative juice runoff (PJR), delestage (D), and extended maceration (EM) were the process assayed on grapes from Tempranillo variety cultivated in a warm climate zone. Enological and color parameters were determined at stemmed-crushed, pressed, bottled and after 4 months aged in bottle. Significant differences were found in color intensity, percentage of red and blue, and hue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 26 publications
5
31
0
3
Order By: Relevance
“…The cold prefermentative process did not increase the anthocyanin levels; control wines had higher contents of these pigments in every vintage (Fig. 4) that agrees to the results of many papers Pérez-Lamela et al 2007;Puertas et al 2008;Gil-Muñoz et al 2009;Gambacorta et al 2011). However, several works showed an increase in the anthocyanin contents of wines produced by pre-fermentative maceration at low temperature (Table 1), affect strongly the effect of the pre-fermentative skin contact on the release of these compounds.…”
Section: Anthocyanin Composition Of Winessupporting
confidence: 90%
See 1 more Smart Citation
“…The cold prefermentative process did not increase the anthocyanin levels; control wines had higher contents of these pigments in every vintage (Fig. 4) that agrees to the results of many papers Pérez-Lamela et al 2007;Puertas et al 2008;Gil-Muñoz et al 2009;Gambacorta et al 2011). However, several works showed an increase in the anthocyanin contents of wines produced by pre-fermentative maceration at low temperature (Table 1), affect strongly the effect of the pre-fermentative skin contact on the release of these compounds.…”
Section: Anthocyanin Composition Of Winessupporting
confidence: 90%
“…The results obtained in this study support the conclusion that anthocyanin profile of wines is mostly dependent on the grape variety rather than the winemaking technology (Puertas et al 2008;González-Neves et al 2010a). Nevertheless, the effect of technology on the anthocyanin composition of wines needs to be further investigated, since it seems to be linked to the intrinsic characteristics of grapes in terms of ripening and richness in phenols (Gambacorta et al 2011).…”
Section: Anthocyanin Profile Of Winessupporting
confidence: 78%
“…Thus, Couasnon (1999) found an increase in the total polyphenol index of 51% and an increase in the total concentration of anthocyanins of 52% with respect to the control wine in Merlot wines pre-fermentative macerated with dry ice. Álvarez, Aleixandre, García, and Lizama (2006) in Monastrell wines; Gómez-Míguez et al (2007)in Syrah wines; Gil-Muñoz et al (2009) in Cabernet Sauvignon and Syrah; Puertas, Guerrero, Jurado, Jiménez, and Cantos-Villar (2008) and Gordillo, López-Infante, Ramírez-Pérez, González-Miret, and Heredia (2010) in Tempranillo grapes, also found a positive effect of cold pre-fermentative maceration on phenolic composition and colour of red wines, although the results obtained in these works do not always coincide and they were not as good as those reported by Couasnon (1999). On the other hand, Pérez-Lamela, García-Falcón, SimalGándara, and Orriols-Fernández (2007) and Soto-Vázquez, Río-Segade, and Orriols-Fernández (2010) did not find a substantial improvement in colour characteristics of Sousón, Brancellao and Mencía cold pre-fermentative macerated wines.…”
Section: Introductionmentioning
confidence: 96%
“…Couasnon (1999), who assessed the effects of pre-fermentative maceration on Merlot wine, reported that dry ice-treated wine had a higher content of total polyphenols and anthocyanins than control wine. The positive effects of cold pre-fermentative maceration on phenolic extraction and wine colour have been reported in several wine varieties, including Monastrell (Álvarez et al, 2006), Syrah (Gómez-Míguez et al, 2007), Cabernet Sauvignon (Gil-Muñoz et al, 2009) and Tempranillo (Puertas et al, 2008;Gordillo et al, 2010). In contrast, Pérez-Lamela et al (2007) and Soto-Vázquez et al (2010) reported insignificant colour improvements in Sousón, Brancellao and Mencía wines following pre-fermentative cold maceration.…”
Section: Introductionmentioning
confidence: 94%